Potential Factors to Enhance Students' STEM College Learning and Career Orientation - Rivera, Hector; Li, Jui-Teng (Frontiers in Education, 2020)
In this study, we highlight the importance of high school students having a college-attending and career-ready mindset in STEM fields. With this purpose, we adopted a stepwise multiple regression analysis to determine which variables are significant predictors of students’ STEM college learning and career orientation. The participants were 1105 high school students from nine randomly selected high schools across greater Houston Texas. 42% of the variance on STEM college learning and career orientation as an outcome variable can be explained by six predictor variables: (a) parental involvement; (b) STEM related activities engagement; (c) academic experience; (d) teacher effective pedagogy; (e) technology/facilities; and (f) self-esteem. The results indicate that when students received support from teachers and parents, they could develop more positive attitudes towards future post-education and career pathways in STEM fields.